THE EFFECTS OF BRITISH COLONIALISM ON THE IRISH LAW OF SUCCESSION - Rath-Boșca, Laura Dumitrana (International Journal of Legal and Social Order, 2025)
Considering the excesses that had been committed over eight centuries, the Anglo-Irish rivalry had reached grotesque proportions over time. The English sought to exercise total control over the British Isles, but the Irish consistently opposed it, which gave rise to a mutual antipathy in the collective psyche. Ireland had, before it came under English rule, its own system of law, dating back to Celtic times and existing until the 17th century, when English common law replaced it. This was Brehon Law, consisting of customs passed down orally from one generation to another and administered by the Brehons, the successors of the Celtic Druids. Although similar to judges, the Brehons were more of an arbiter (Katharine Simms, 2000, p. 79) whose task was to preserve and interpret the law rather than to extend it. In the early 17th century, the military victory against Hugh O'Neill, Earl of Tyrone was decisive, decisive and represented a first stage in the English domination of Ireland. Political consolidation was achieved by legal means and represented the second stage in the process of English domination. These events led to the legislative reform of the early 17th century.[1]Sir John Davies argued that the eradication of Irish Brehon law was justified by the right of conquest and that Brehon law resembled "a barbarous and indecent custom". [1]Sir John Davies, who studied briefly with Paul Merula at Leyden in the Netherlands, was one of the most important Crown lawyers who worked to reform the Irish administration in the early 17th century. He served as Solicitor General and Attorney General and had a significant influence on Irish law, administration and jurisprudence. His legacy is highlighted in his Irish Law Reports.